2022
DOI: 10.3389/fvets.2022.1053730
|View full text |Cite
|
Sign up to set email alerts
|

High energy diet of beef cows during gestation promoted growth performance of calves by improving placental nutrients transport

Abstract: The aim of this study was to explore the effects of dietary energy level during gestation on growth performance and serum parameters in offspring using beef cattle as research objects. Additionally, the gene expressions associated with nutrients transport in the placenta were evaluated. Eighteen Simmental crossbred cows (body weight = 338.44 ± 16.03 kg and 760 ± 6 days of age) were randomly assigned to 3 dietary treatment groups: low energy (LE, metabolic energy = 8.76 MJ/kg), medium (ME, 9.47 MJ/kg) and high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…A study on goose liver cells found that glucose can regulate PI3K-Akt-mTOR activation to promote goose liver cell proliferation [38]. Consistent with this result, high dietary energy upregulated the gene expression of transporters in placental tissue [14], indicating that glucose transport in the placenta is affected by glucose concentration [39]. GLUT1 can efficiently transport glucose to the placental trophoblast ectoderm and subsequently to the placental vascular system to provide energy for the fetus in sows [21].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A study on goose liver cells found that glucose can regulate PI3K-Akt-mTOR activation to promote goose liver cell proliferation [38]. Consistent with this result, high dietary energy upregulated the gene expression of transporters in placental tissue [14], indicating that glucose transport in the placenta is affected by glucose concentration [39]. GLUT1 can efficiently transport glucose to the placental trophoblast ectoderm and subsequently to the placental vascular system to provide energy for the fetus in sows [21].…”
Section: Discussionmentioning
confidence: 82%
“…The glucose transporters (GLUTs) are the main transporters of glucose uptake by the PTC [ 8 , 9 ], and the glucose transporter 1 (GLUT1) [ 10 ], glucose transporter 3 (GLUT3) [ 11 , 12 ], and glucose transporter 4 (GLUT4) are highly expressed in placental tissue [ 13 ]. Our recent in vivo study showed that the mRNA abundance of GLUT1 and GLUT3 in placental tissue increased with the increase of dietary energy levels during pregnancy and was positively correlated with the birth weight and serum glucose concentration in newborn calves [ 14 ]. The primary glucose transporters in the placenta consist of GLUT1 and GLUT3, both of which regulate the transportation of glucose from the maternal to the fetal circulation [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%